Pseudomonas 42P4 and Cellulosimicrobium 60I1 as a sustainable approach to increase growth, development, and productivity in pepper plants - Lobato-Ureche, Miguel Andrés; Pérez-Rodriguez, María Micaela; Segura, Diana; Monasterio, Romina; Cohen, Ana Carmen (Frontiers in Sustainable Food Systems, 2023)
The production of pepper plants for industrial use is not enough to satisfy the demand of consumers and agrochemicals are frequently used to increase production. In this study four native plant growth promoting rhizobacteria (PGPR) was tested as an alternative to select the most effective to enhance growth, development, and productivity of pepper plants. Seedlings were inoculated with Pseudomonas 42P4, Cellulosimicrobium 60I1, Ochrobactrum 53F, Enterobacter 64S1 and cultivated on pots in the greenhouse and the morphological, biochemical, and physiological parameters were determined. In addition, the phenolic compound profiles were evaluated. All four strains increased the different parameters evaluated but Pseudomonas 42P4 and Cellulosimicrobium 60I1 were the most effective strains, improving leaf and root dry weight, stem diameter, nitrogen level, stomatal conductance, chlorophyll quantum efficiency, chlorophyll SPAD index, total chlorophyll and carotenoid levels, number of flowers and fruits per plant, and the length, diameter and dry weight of the fruit. Also, these strains modified the phenolic compound profiles, and eighteen compounds were quantified. . Pseudomonas 42P4 inoculation modified the phenolic compound profile similarly to the Fertilized treatment and induced the synthesis of different endogenous compounds in the flavonoid family, also increasing catechin, naringin, naringenin, myricetin, procyanidin B1, epigallocatechin-gallate, cinnamic and ferulic acids related to antioxidant activity and catechin, cinnamic and ferulic acids related to the induced systemic response. Pseudomonas 42P4 can be used as a bioinoculant in pepper plants to enable better agronomic management, decreasing the use of chemical fertilizer to contribute to sustainable agriculture.